Poland, 1918-1945 : an interpretive and documentary history of the Second Republic - Stachura, Peter D. (Routledge, 2004)
Poland, 1918-1945 is a challenging, revisionist analysis and interpretation, supported by documentary evidence, of a crucial and controversial period in Poland's recent history.